2019
DOI: 10.21608/ejmm.2019.283189
|View full text |Cite
|
Sign up to set email alerts
|

Could Training Programs Eliminate Hospital Environmental Surfaces Contamination with Multidrug Resistant Bacteria

Abstract: Hospital environment could be a risk for transmission of nosocomial infections. Objectives: This study aimed to evaluate the effect of training program on the elimination of microbial contamination of hospital environmental surfaces, devices and health care workers (HCWs) hands. Methodology: Two phases interventional study was conducted for basal evaluation and training of HCWs and housekeepers on standard precautions with evaluation of environmental surfaces, devices and hands contamination at basal level bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
2
3
0
Order By: Relevance
“…From all previous results we found that the education program in phase II succeeded partially in achieving a statistically significant reduction (p ≤ 0.05 at all sites) in contamination level for all samples' sites. This was in agreement with Bassyouni et al (8) , who also found a statistically significant reduction of contamination level after education at all departments included in their study. Also, Hefzy et al (8) found a significant improvement after educational intervention on contamination level in outpatient clinics.…”
Section: (13)supporting
confidence: 93%
See 3 more Smart Citations
“…From all previous results we found that the education program in phase II succeeded partially in achieving a statistically significant reduction (p ≤ 0.05 at all sites) in contamination level for all samples' sites. This was in agreement with Bassyouni et al (8) , who also found a statistically significant reduction of contamination level after education at all departments included in their study. Also, Hefzy et al (8) found a significant improvement after educational intervention on contamination level in outpatient clinics.…”
Section: (13)supporting
confidence: 93%
“…This was in agreement with Bassyouni et al (8) , who also found a statistically significant reduction of contamination level after education at all departments included in their study. Also, Hefzy et al (8) found a significant improvement after educational intervention on contamination level in outpatient clinics. also is consistent with Santos et al (12) , who found a positive impact for educational intervention on surfaces cleaning and disinfection.…”
Section: (13)supporting
confidence: 93%
See 2 more Smart Citations
“…The clear non-compliance with the international ( 14) as well as Egyptian guidelines (33) for infection control regarding oors, machines, linen, and highly contacted surfaces by patients as doorknobs and window knobs has led to an ineffective reduction in the bacterial counts in the swabbed areas indicating the need for proper inspection and assurance of strict compliance with these regulations in the unit (27,34,35).…”
Section: Discussionmentioning
confidence: 99%